If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -64 = -56t Solving -64 = -56t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '56t' to each side of the equation. -64 + 56t = -56t + 56t Combine like terms: -56t + 56t = 0 -64 + 56t = 0 Add '64' to each side of the equation. -64 + 64 + 56t = 0 + 64 Combine like terms: -64 + 64 = 0 0 + 56t = 0 + 64 56t = 0 + 64 Combine like terms: 0 + 64 = 64 56t = 64 Divide each side by '56'. t = 1.142857143 Simplifying t = 1.142857143
| 8*4(64-8)7+8= | | 4y^4-25y^2+144=0 | | (5x-3)/4 | | 7x+4+x+6+2x=180 | | 1.25x+4.5=.8+.25x | | (3x-4x+2y)*(2y+3y+2x)=-x+xy+10y | | -11x-34=43 | | (2x+10)+(3x+50)=90 | | 7.25x+y=443.75 | | y=60x+40 | | (3x-4x+2y)*(2y+3y-2x)=-x+xy+10y | | X+13=6x-32 | | (1/9)x-(1/3)=(-1/6)x-(1/2) | | 1/4a=-1/32 | | -2(3x+6)=-15x | | 3/5x-4(0)=1 | | (3/5)x-2 | | 10=-3/4c | | 4/9x4/9x4/9 | | .875x-2=-.9375x+3 | | 7n+5=8n | | 3/5x-4y=1 | | 10x+5n=100 | | T=-16t^2+0t+29000 | | 95-76=19 | | 3A+6(A+2)= | | 3(6x-1)-4(2x-16)=3(3x+3)-4 | | T=-16t^2+Vt+s | | 3r^2-2r=-5 | | 7x(x+6)=6 | | 3r^2-2r+5=0 | | y^4-y^2+2=0 |